Communicable Diseases Intelligence volume 14 issue 8 - 23 April 1990 - whole issue - No author listed (Communicable Diseases Intelligence, 1990)
Whole-issue pdf, comprising: Viruses, Chlamydias, Coxiellas, Rickettsias and Mycoplasmas Reporting Scheme [see correction in CDI 90/9, page 15] Overseas briefs Original articles Australian encephalitis fatality - update [update to article in previous issue CDI 14/8, pages 3-4] Increase in meningococcal infections detected at the Royal Children's Hospital, Melbourne Legionella pneumophila: molecular epidemiology supplements 'gumshoe' epidemiology Legionella pneumophila: outbreak associated with a mist machine in a retail food store [USA] AIDS and HIV surveillance, Australia: 23 Febrauary 1990 Influenza update 1989-90 Reporting Tables: Australia - Communicable Diseases Intelligence Period 29/3/90 to 29/4/90